Demographic Processes in the Western Part of the Armenian Highland (Late XV-XIV Centuries BC) - Aram Kosyan (Banber Arevelagitut'yan Instituti, 2025)
The cuneiform Hittite texts of the XV-XIV centuries BC contain important information dealing with at least two different population movements happened along the Upper Euphrates region. First of these is fixed in the treaty signed between the Hittite king Tudhaliyaš II (second part of the XV century BC) and Šunaššura, king of Kizzuwatna. The second migration took place later, during the reign of Tudhaliyaš III. This second migration is of interest since in that population movement was involved a great number of people from different parts of Asia Minor. The study of several Hittite prayers compiled during the reign of Arnuwandaš I allow to assume that this second migration is definitely connected with continuous famine, hunger, plague and attacks of neighboring countries which could force the population of several regions to migrate first to Išuwa and from there to hayaša.